Origin of the left common carotid artery from ascending aorta in association with tetralogy of Fallot and hypoplastic right cervical aortic arch. Issue 12 (6th November 2022) - Vidiyala, Pujitha; Ojha, Vineeta; Ramakrishnan, Sivasubramanian; Jagia, Priya
Abstract: We present a case of a 6‐year‐old girl with tetralogy of Fallot (TOF) and hypoplastic aortic arch with anomalous origin of left common carotid artery from the ascending aorta. The case highlights the importance of screening for abnormalities of aortic arch and arch vessels in TOF patients for accurate presurgical planning and to predict the postoperative outcomes.